EVA blends for 3D printing of sports shoes - Tan, Michelle Chor Hui (Nanyang Technological University, 2020)
The huge development in technology and the sports industries brought about the need for more materials to be explored in the application of 3D printing. Ethylene-vinyl acetate (EVA) has been used extensively in the shoe manufacturing industry as midsole foams, but unfortunately, this material has not been 3D printed successfully due to its high viscosity and low elastic modulus associated with different EVA grades. Ecological concerns have also prompt awareness in EVA materials to be innovated with certain biodegradation property. This report investigates the relationship of EVA material with PEBAX, adhesive grade EVA, Licowax OP and paraffin wax, in terms of the modulation effects in viscosity properties where preparation of these different blend ratios will be carried out by extrusion process. Transesterification reaction of EVA and PLA biodegradable polymer by reactive extrusion with titanium (IV) isopropoxide, zinc acetate dihydrate, antimony (III) oxide and tin (II) 2-ethylhexanoate catalysts were also executed to study the influence of these blends with copolymer synthesis. The results were supported by the rheology, thermal and characterisation analysis which revealed viscosity drop and also demonstrated substantial evidence for a possibility in the presence of copolymer in blends.